Analysis of technical efficiency and determining factors of the broiler business in North Sulawesi - Lidya Siulce Kalangi; Stanly Oktavianus Bryneer Lombogia; Jeane Pandey; Andi Yulyani Fadwiwati (Universitas Sebelas Maret, 2022)
Objective: The broiler business with the partnership model has become a choice of society in improving their living. In certain circumstances, however, broiler farmers receive income far beyond their expectations due to declining production, because of some impacts of inefficient input utilization and worse management. The research, then, aims to estimate the technical efficiency of broiler farming business with an open house system and a partnership business pattern, as well as to analyze the determining factors.Methods: The purposive sampling was employed to identify 80 farmers. In detail, the parameter of production function of the Stochastic Frontier was estimated by using Maximum Likelihood Estimations (MLE) method and Frontier 4.1 program. Results: The estimated value in the statistic model (γ=0.8634) depicts that the hypothetical result of the production function model was assumedly better, so the production function of Cobb-Douglas was able to explain the existing data related to a phenomenon of the technical inefficiency in broiler business. The calculation result of the value of restriction parameter of LR test was 89.99, was greater than the critical value of the Kodde and Palm Table (=19.384), by the significance level at p<0.01. This means the existing inefficiency effects in the stochastic model. Further, the value of sigma square with the parameter value of 0.0133 was statistically significant by the trust level of 99%, describing that the production variation contributed by technical inefficiency was 1.33%. Conclusions: In conclusion, the value of technical efficiency obtained by broiler farmers under the partnership model in the open-house system was 0.95. Then, the determining variables of the broiler production were feeds, vitamins, medicine, working hours, and the total of electricity. Determinant variables that could reduce technical inefficiency were age, farming experience, and ownership status of lands/cages.